EFFECT OF FLIPPED LEARNING ON COGNITIVE LOAD: A HIGHER EDUCATION RESEARCH - Celal Karaca; Mehmet Akif Ocak (Journal of Learning and Teaching in Digital Age, 2017)
The purpose of this study is to determine the effect of the flipped learning method on the cognitive load of the students. The study was conducted with a sample of 160 people who were trained in Department of Mechanical Engineering for algorithms and programming courses at a higher education level. The study, which lasted for 8 weeks, has a semi-experimental design. A 9-point scale developed by Paas and Van Merrienboer (1993) was used for cognitive load measurements. At the end of the weekly courses, the scale was filled by the experimental and control groups. Independent sample t test was applied through SPSS 24 program to the obtained data. In both instances, the cognitive load in the experimental group in which the flipped learning method was applied was found to be lower than the cognitive load in the control group in which traditional face-to-face training was applied. As a result, it can be said that flipped learning, if well structured, is a method reducing cognitive load.